The Ethics of AI in Warfare: Risks and Responsibilities (Journal of responsible AI & ethics, 2026)
The integration of Artificial Intelligence (AI) into military systems has sparked significant debate about the ethical implications of its use in warfare. AI technologies, such as autonomous weapons systems, surveillance tools, and cyber warfare applications, hold the potential to change the landscape of modern warfare, offering both strategic advantages and serious ethical risks. The ethical concerns regarding AI in warfare focus on issues such as accountability, autonomy, human control, and the potential for unintended consequences. This paper examines the ethical dilemmas surrounding the use of AI in military contexts, analyzing the risks involved and the responsibilities of developers, policymakers, and military leaders in ensuring that AI technologies are used in ways that comply with international humanitarian laws and ethical principles. The study also explores the concept of just war theory in the context of AI, considering whether autonomous machines can be held accountable for their actions in warfare. The paper concludes by offering recommendations for ethical frameworks, regulatory standards, and accountability mechanisms to guide the development and deployment of AI in warfare, ensuring that these technologies are used responsibly and ethically.